Volatile Solid Additive‐Assisted Sequential Deposition Enables 18.42% Efficiency in Organic Solar Cells. Issue 9 (24th January 2022) - Qin, Jianqiang; Yang, Qianguang; Oh, Jiyeon; Chen, Shanshan; Odunmbaku, George Omololu; Ouedraogo, Nabonswendé Aïda Nadège; Yang, Changduk; Sun, Kuan; Lu, Shirong
Abstract: Morphology optimization of active layer plays a critical role in improving the performance of organic solar cells (OSCs). In this work, a volatile solid additive‐assisted sequential deposition (SD) strategy is reported to regulate the molecular order and phase separation in solid state. The OSC adopts polymer donor D18‐Cl and acceptor N3 as active layer, as well as 1, 4‐diiodobenzene (DIB) as volatile additive. Compared to the D18‐Cl:N3 (one‐time deposition of mixture) and D18‐Cl/N3 (SD) platforms, the D18‐Cl/N3(DIB) device based on DIB‐assisted SD method exhibits a finer phase separation with greatly enhanced molecular crystallinity. The optimal morphology delivers superior charge transport and extraction, offering a champion power conversion efficiency of 18.42% with significantly enhanced short‐circuit current density ( J sc ) of 27.18 mA cm −2 and fill factor of 78.8%. This is one of the best performances in binary SD OSCs to date. Angle‐dependent grazing‐incidence wide‐angle X‐ray scattering technique effectively reveals the vertical phase separation and molecular crystallinity of the active layer. This work demonstrates the combination of volatile solid additive and sequential deposition is an effective method to develop high‐performance OSCs. Abstract : High‐performance organic solar cells (OSCs) based on D18‐Cl and N3 are fabricated by combining volatile solid additive 1, 4‐diiodobenzene (DIB) with sequential deposition (SD) strategy. The formed D18‐Cl/N3(DIB) film exhibits favorable phase separation and enhanced crystallinity. The optimized morphology enables a remarkable power conversion efficiency of 18.42%, which is one of the highest performances in binary SD OSCs to date.